2017
DOI: 10.1126/science.aah6442
|View full text |Cite
|
Sign up to set email alerts
|

Quantized electric multipole insulators

Abstract: The Berry phase provides a modern formulation of electric polarization in crystals. We extend this concept to higher electric multipole moments and determine the necessary conditions and minimal models for which the quadrupole and octupole moments are topologically quantized electromagnetic observables. Such systems exhibit gapped boundaries that are themselves lower-dimensional topological phases. Furthermore, they host topologically protected corner states carrying fractional charge, exhibiting fractionaliza… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

33
1,902
2
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,811 publications
(1,994 citation statements)
references
References 40 publications
(69 reference statements)
33
1,902
2
4
Order By: Relevance
“…However, crystal symmetries can be a key to ensure that a natural surface termination -i.e., a surface termination that respects the crystal symmetries -automatically leads to a nontrivial higher-order topological phase. For example, Benalcazar et al employed a combination of multiple reflection symmetries [9], whereas Schindler et al considered C 4 T symmetry, the product of a π/2 rotation and time reversal, as well as a model with reflection symmetry [7].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, crystal symmetries can be a key to ensure that a natural surface termination -i.e., a surface termination that respects the crystal symmetries -automatically leads to a nontrivial higher-order topological phase. For example, Benalcazar et al employed a combination of multiple reflection symmetries [9], whereas Schindler et al considered C 4 T symmetry, the product of a π/2 rotation and time reversal, as well as a model with reflection symmetry [7].…”
mentioning
confidence: 99%
“…For example, a second-order topological insulator in two dimensions (d = 2) has zeroenergy states at corners, but a gapped bulk and no gapless edge states. Earlier examples of higher-order topological insulators and superconductors avant la lettre appeared in works by Benalcazar et al [8][9][10] (see also [11,12]), who considered insulators and superconductors with protected corner states in d = 2 and d = 3 [13]. Sitte et al showed that a threedimensional topological insulator in a magnetic field of generic direction also acquires the characteristics of a second-order topological Chern insulator, with chiral states moving along the sample edges [14].…”
mentioning
confidence: 99%
“…The theoretical prediction of higher order systems rests on a generalization of electric dipole moments to multipole moments that are quantized (having only specific discrete values) 5,6 . Whereas conventional topologi cal insulators are related to dipoles, higher order insulators are related to quadrupoles, octupoles, and so on.…”
Section: Waves Corneredmentioning
confidence: 99%
“…The presence of mela nin can trigger an immune response in the infected organism 4 , but how this occurs was unknown. On page 382, Stappers et al 5 report the identification of a protein that can recog nize a type of melanin produced by the fungus Aspergillus fumigatus. Their finding illuminates the immune system response to a fungal infection that can be lethal in people who have a suppressed immune system, such as those who have undergone transplantation surgery 6 .…”
Section: A R T U R O C a S A D E Va L Lmentioning
confidence: 99%
“…For example, a second-order topological insulator in two dimensions (d ¼ 2) has zero-energy states at corners, but a gapped bulk and no gapless edge states. Earlier examples of higher-order topological insulators and superconductors avant la lettre appeared in works by Benalcazar et al [8][9][10] (see also Refs. [11,12]), who considered insulators and superconductors with protected corner states in d ¼ 2 and d ¼ 3 [13].…”
mentioning
confidence: 99%